OPTIMALISASI DIGITAL PADA UMKM BPK MEDAN DAN KEDAI KOPI MEDAN MELALUI SOSIAL MEDIA DAN WEBSITE - puput eka patmalasari; Levira Dwi Hari Febyani; Putry Natasya Tamawiwy; Ranti Sapitri (DIMASEKA, 2024)
The development of digital technology provides great opportunities for Micro, Small and Medium Enterprises (MSMEs) to increase marketing effectiveness and competitiveness. This community service activity aims to assist UMKM BPK Medan and Kedai Kopi Medan in optimizing digital marketing through training in website creation, social media management, registration on the Gojek platform, as well as content creation and content calendars. The method used is Participatory Action Research (PAR), which involves active participation of business actors in the entire process. The results of the activity show that the implementation of digital marketing can increase credibility, expand audience reach, and facilitate interaction with customers. The website created serves as a business portfolio, while social media and the Gojek platform support promotion and ease of service. This training has a significant impact on the marketing structure of MSMEs, making them more professional and relevant to the development of the digital market.